Product Lifecycle Management pre-study: An investigative case at Industrial Automation, ABB AB - Nandakumar, Lokesh; Radhakrishnan Hariharan, Varun (My University, 2020)
The concept of Product Lifecycle Management (PLM) is becoming popular than ever. Industries are growingly understanding the necessity to incorporate this strategy as an essential business element. This research presents an overview of how a backbone PLM is seemingly significant for ABB Industrial Automation, Business Unit X (masked name). The internal organizational quest to identify a central repository to maintain product-related data and to re-establish ABB products as the central source of truth is investigated in this pre-study. In the earlier phases of this study, the current organizational landscape is presented from the qualitative data gathered through interviews, existing literature, and benchmarking. This is then followed by analyzing the latest industrial trends and ABB's global vision to achieve a completely data-driven future. A thorough study of various legal and sustainable requirements are also projected in this pre-study. The gaps existing between the current IS/IT landscape and projected future requirements are bridged by proposing a PLM solution, identifying a suitable vendor, and calculating Return of Investment. Throughout the report, the complexity of adopting a PLM concept is presented as well as the benefits and uncertainties which come along with such an investment.